Keterlibatan Guru dalam Pelayanan Ibadah Sekolah Minggu: Upaya Membentuk Karakter Anak Melalui Metode Bermain di Pulau Teluk Nipah - Rismag Dalena Florentina Monica Br Manurung; Jenri Prada Sibarani; Betaria Siahaan; Sylvia Natalia; Ivan Ivan; Yunardi Kristian Zega; Daniel Agustin (Sekolah Tinggi Teologi Real Batam, 2021)
The purpose of this Community Service is to encourage Sunday school teachers on the island of Teluk Nipah to be involved in shaping the character of the children being taught. This is because, in reality on the island of Teluk Nipah, the involvement of Sunday school teachers in the formation of the character of the children being taught is still very low, this can be seen from the Sunday school worship activities that have been carried out. The method used in this Community Service activity is worship services by making games that can foster children's enthusiasm to learn God's word. The result of this activity is that there are as many as 87% of children who are enthusiastically present when participating in a series of worship service activities with games. The involvement of Sunday school teachers in this activity, including: opening the hearts of children to come to worship, diligently reading God's word, and children can apply cooperation, honesty, and togetherness.Keywords: Teacher, Character, Sunday school, Played, Nipah Bay Island AbstrakTujuan dari Pengabdian kepada Masyarakat (PkM) ini adalah untuk mendorong para guru sekolah minggu di pulau Teluk Nipah agar terlibat dalam pembentukan karakter anak-anak yang diajar. Pada realitanya di pulau Teluk Nipah keterlibatan guru sekolah minggu dalam pembentukan karakter anak-anak yang diajar masih sangat kurang, hal tersebut dapat dilihat dari kegiatan ibadah sekolah minggu yang telah dilaksanakan. Metode yang digunakan dalam kegiatan Pengabdian kepada Masyarakat ini adalah pelayanan ibadah dengan membuat permainan yang dapat menumbuhkan semangat anak-anak agar belajar firman Tuhan. Hasil dari kegiatan ini adalah ada sebanyak 87% anak-anak yang antusias hadir saat mengikuti rangkaian kegiatan pelayanan ibadah dengan permainan. Adapun keterlibatan guru sekolah minggu dalam kegiatan ini, di antaranya: kegiatan bermain tebak lagu, tebak gambar, dan UNO.Kata kunci: Guru, Karakter, Sekolah Minggu, Bermain, Pulau Teluk Nipah